ANALYSIS OF THE PHYSICOCHEMICAL PROPERTIES OF POLYVINYL CHLORIDE AND THE IMPORTANCE OF MINERAL FILLERS IN INCREASING ITS FIRE RESISTANCE - Abdirashidov, Durbek; Turaev, Khayit; Tajiyev, Panji (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This article explores on the role and importance of fire-resistant composite materials in the construction industry, the specific properties of polyvinylchloride (PVC) in fire-resistant composite materials, an analysis of its physico-chemical properties, and the need for mineral fillers and additives to increase the fire resistance of PVC.